Peningkatan Pemahaman dan Aplikasi Konsep Melalui Pendekatan Contextual Teaching and Learning - Dedy Juliandri Panjaitan (Jurnal MathEducation Nusantara, 2018)
Abstrak Constructivistic learning is a learning with students construct their own knowledge and understanding, it is related to the process of learning to teach mathematics. The existence of Constructivistic paradigm affects the learning strategy applied by the teacher. In the learning rocess acts as a facilitator and students as an active learner so that learning is not centered on the teacher but centered on the students. Implementation of mathematics learning process is expected to use constructivist-oriented learning model, one of which is learning cycle learning model. this article aims to know the improvement of understanding and application of mathematical concepts of students with contextual approach Teaching and Learning through Learning Cycle on the material of building flat side space. This article is the result of Class Action Research where the cycle cycle review consists of four stages. Based on the results of the study concluded that the contextual approach through learning Cycle can improve understanding and application of concepts. Keywords: Learning Cycle, contextual Teaching and Learning, student center